Distribution of BoLA-DRB3 Allelic Frequencies and Identification of Two New Alleles in Iranian Buffalo Breed. (14th February 2012) - Mosafer, J.; Heydarpour, M.; Manshad, E.; Russell, G.; Sulimova, G. E.
Abstract : The role of the major histocompatibility complex (MHC) in the immune response makes it an attractive candidate gene for associations with disease resistance and susceptibility. This study describes genetic variability in the BoLA-DRB3 in Iranian buffaloes. Heminested PCR-RFLP method was used to identify the frequency of BoLA-DRB3 alleles. The BoLA-DRB3 locus is highly polymorphic in the study herd (12 alleles). Almost 63.50% of the alleles were accounted for by four alleles ( BoLA-DRB3.2 *48, *20, *21, and obe ) in Iranian buffalo. The DRB3.2 *48 allele frequency (24.20%) was higher than the others. The frequencies of the DRB3.2 *20 and DRB3.2 *21 are 14.52 and 14.00, respectively, and obe and gbb have a new pattern. Significant distinctions have been found between Iranian buffalo and other cattle breed studied. In the Iranian buffaloes studied alleles associated with resistance to various diseases are found.